New Public Management of AREF Casa-Settat Schools: Constraints and Performance Improvement - Abouddaka, Ismail; Bassiri, Mustapha; Tridane, Malika; Atibi, Azzeddine; Belaaouad, Said (TECCIENCIA, 2022)
Objects of study aims to comprehend the integration of new managerial strategies in the administrative reform of public school, the implementation of the NPM principles allowing the improvement of the quality of the piloting process and of pragmatic action-oriented mechanisms. This article studies the level of operationalization and the streamling of public administration management practices, while trying to identify constraints and assessing improvement plans. Theoretical Frame: The foundations of the study make it possible to balance the theoretical, empirical and scientific aspects of NPM. On a theoretical level, it offers a scope of analysis of new public management practices. We will also consider the doctrinal approaches and principles in close relation to the school setting. Recommended Methodology: Our research methodology is an exploratory descriptive study, the data collection instruments are mainly the documentary study, the analysis of management practices of the people involved and the stakeholders of the establishment. It is based on the government program model which is built on 4 components: management autonomy, evaluation, institutional openness and management capacities support. Results: The results show that the improvement of schools requires the implementation of a managed, controlled and dynamic steering system that is oriented towards the search for organizational performance. This improvement would be through the integration of NPM practices that aim to optimize performance through private sector practice.